Scanning electron microscopy observations of the mandibles of scaptotrigona postica workers (Hymenoptera, apoidea) - Stort, Antonio Carlos [UNESP]; Bueno de Moraes, Mônica M. [UNESP]; Barelli, Nilso [UNESP] (Taylor & Francis, 1986)
Mandibles of Scaptotrigona postica, stingless bees with a highly evolved social organization and a system of communication based on mandibular gland secretions, were studied by SEM. In the frontal region, which exhibits both smooth and reticulated chitin, there are two fine grooves which delimit a region located in a lower plane. Ventral examination of the mandible showed the presence of a concave region containing a cutting blade, and of hairs of different sizes, some cavity-like structures, and a large number of campaniform sensilla. The mandibular gland opens on the internal part of the articulation of the mandible with the head outward through an orifice which is approximately elliptical in shape and which has reinforced margins and an elevated part close to one end. Throughout the ventral region of the mandibles are pores which may be grouped or isolated and which may represent sites of external elimination of the secretions of the intramandibular glands. © 1986 International Bee Research Association.